IMPLEMENTATION OF FUSION TALK APPLICATION IN NARRATIVE WRITING - Indra Perdana (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2016)
This study aims to determine: (1) differences in narrative writing between the groups using Talk Fusion applications and groups not using the Talk Fusion applications, and (2) the effectiveness of the use of Talk Fusion applications in narrative writing for semester VI students of University of Palangka Raya. The study was an experimental study. The design of the study was Pre-test and Post-test Control Group Design. There are two variables in this study, namely the independent variable in the form of Talk Fusion applications and the dependent variable namely the narrative writing. The results of t-test calculation shows t scores that is greater than t table (th: 4.711> tt: 1.980) at a significance level of 5% and db 70. This shows that there are significant differences in the narrative writing between groups by learning by using Talk Fusion applications and the group learning without the use of Talk Fusion applications. Scheffe test calculation results showed F count is higher than F table (Fh: 22.194> Ft: 3.98) with 70 db and at a significance level of 5% of 36 students. This indicates that the value of the struggle of a character in biographies by using Talk Fusion applications are more effective than learning character that is not using Talk Fusion applications in the control group. Thus, it can be concluded that the use of Talk Fusion applications can improve the ability to write narrative.